Development And Validation Of Project-Based Module For Selected Topics In Biology - C. Cruz, Lord Ian; C. Rivera, Kimberly (CV. Inara, 2022)
This paper focused on the development of validation of a project-based learning module for selected topics in Biology. Project-Based Learning is deemed to promote holistic development of the learners especially in relation to biology for junior high school. The development phase involved the identification of the least learned competencies in biology that involved topics about cells, microorganism, digestive system and biodiversity, photosynthesis, cellular respiration, and ecosystems and evolution. The development phase also involved the formulation of the general layout of the module as well as the creation of project-based learning activities, as well as other related exercises and activities and rooms or reflections, and conclusions. The module is described according to the module design, module content, and the project-based learning content. The module design is characterized into the cover page, preface and table of contents, and the module content per grade levels themselves. For the module content, it involved the activities, lessons, exercises, and projects that come with each of the topic per grade level. Lastly, the PBL content focused on the structure of Project-based learning itself, which deemed to promote holistic learning among the learners especially when it comes to other skills such as creativity, problem-solving skills, and critical thinking. The learning module also underwent the process of validation. There were ten identified validators for the learning module who were given a set of rubrics that assisted them in terms of evaluating the researcher-made project-based learning module. Through the validation process, the module was marked as excellent, as all the expected elements of the modules were met.